Demographic, Maternal and Obstetrical Factors Associated with Infantile Colic (Medical Forum Monthly, 2024)
Objective: To find out the demographic as well as maternal and obstetrical factors associated with infantile colic.Study Design: A case control study.Place and Duration of Study: This study was conducted at the Institute of Child Health, Multan, Pakistan and Pediatrics Department, Services Hospital, Lahore Pakistan from October 2018 to March 2019.Materials and Methods: We enrolled 100 cases and 100 controls from outpatient facilities for this study. Cases were considered as babies of both genders who had IC as per Wessel’s criteria and having age less than 3 months. Controls were babies attending clinic without colic and who were more than 3 weeks to 3 months of age. Demographic, maternal and obstetrical data was recorded and compared between cases and controls.Results: Most of the cases with IC, 53 (53.0%) were females, aged 4 to 6 weeks 53 (53.0%) and were having mixed feeding 38 (38.0%). Mean age of the cases was recorded as 5.2 weeks in comparison to a mean of 6.2 weeks in control group (p < 0.0001). Mean daily sleep duration was recorded to be 9.52 hours vs 13.12 hours in control group (p < 0.0001). Crying at night (p = 0.003) was turned out to be a factor significantly associated with IC (p > 0.05).Conclusion: IC is a frequent problem in younger infants. Night crying and comparatively less sleep time per day was noted babies with IC. Parents handling IC should be motivated and educated about this problem to handle their babies in a better way.